Atmospheric impacts of local sea surface temperatures versus remote drivers during strong South China Sea winter cold tongue events. (7th February 2023) - Seow, Marvin Xiang Ce; Hassim, Muhammad Eeqmal Eesfansyah; Venkatraman, Prasanna; Tozuka, Tomoki
Abstract: Sea surface temperatures (SSTs) in the western part of the South China Sea (SCS) are cooler than in the eastern part in boreal winter, owing to a winter climatological cold tongue (CT). In this study, using a regional atmospheric model configured for the Maritime Continent, we assess the atmospheric impacts of local (or SCS) SSTs versus those from remote drivers (e.g., western tropical Pacific SSTs) during strong CT events with anomalously cool SSTs. In the local run, more rainfall is observed over the eastern SCS, but no significant atmospheric impacts are found over the CT region when SSTs associated with strong CT events are imposed within the SCS while climatological conditions are imposed elsewhere. SCS SST anomalies during strong CT events do not significantly modify the regional wind circulation. The lack of atmospheric response to SSTs over the CT region may be explained by the wintertime mean SSTs (i.e., <27–28°C) over the CT region that are inadequate to trigger deep atmospheric convection, while eastern SCS SSTs are high enough. The increase of anomalous positive moist static energy (MSE) near the sea level over the eastern SCS indicates underlying warm eastern SCS SST anomalies could be influencing positive rainfall anomalies. In the remote run, imposing climatological SCS SSTs but remote SSTs and lateral boundary conditions linked to strong CT events results in cyclonic wind and positive rainfall anomalies over the eastern SCS and Philippines, which are a Matsuno–Gill response to the diabatic heating anomalies over the warm western tropical Pacific SST anomalies. Positive rainfall and cloud cover anomalies associated with the cyclonic wind anomalies are due to the anomalous positive MSE import into the eastern SCS by horizontal advection. Abstract : South China Sea (SCS) cold tongue (CT) sea surface temperature (SST) anomalies linked to strong CT events do not trigger any atmospheric anomalies. In contrast, SST anomalies associated with strong CT events over the eastern SCS and western tropical Pacific and other remote drivers trigger rainfall and/or regional wind circulation changes.